Glucose Sensing Using Hydrogel By Incorporating Phenylboronic Acid Groups - Nadia Baqer Hussein (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Background: Research of glucose detection is important in diabetes management and biosensor development. Taking into account the large amount of water retention, the biocompatibility of hydrogels makes them ideal candidates for glucose detection. The PBA groups, when grafted to hydrogel matrices, improve the glucose-related response of the hydrogels significantly. Objective: To create a novel PBA (phenylboronic acid) holographic glucose sensor, MAAm-co-4VPBA, for uninterrupted monitoring of blood glucose levels, which demonstrates the first successful glucose measurement in whole blood using PBA sensors. Methods: Methylacrylamide (MAAm) was copolymerized with 4-vinyl phenyl boronic acid (4-VPBA) by means of free radical polymerization employing 1,6-hexanedioldiacrylate (HDODA) as a crosslinker and the photoinitiator 1-hydroxycyclohexyl phenyl ketone. The responsive glucose behavior of the resulting polymer was characterized in terms of swelling dynamics, ex vivo flow tests, and error grid analysis mechanisms. Results: The MAAm-co-4VPBA polymer exhibits reversible glucose binding via PBA-diol interactions that allow complexation at different pH and concentration levels. Modulation of the responsive elements of the microcapsules by hydrophobic PBA and hydrophilic MAAm units yields maximum swelling and shrinking dynamics at 37 trail degrees. The sensor successfully detected glucose in opaque biological fluids, blood plasma, without any interference from antibiotics or other therapeutics or endogenous compounds. Ex vivo tests showed real-time glucose monitoring without hysteresis. Most importantly, this work is the first to report the use of PBA-based sensors in whole blood for measuring glucose. Conclusion: The MAAm-co-4VPBA holographic sensor possesses outstanding features such as accurate records and strong resistance to chemicals and slow response to detection, confirming its effectiveness in continuous glucose monitoring. Moreover, the ability to operate in the real world enables the aid in clinical diagnosis of diabetes.